2013
DOI: 10.1007/s00167-013-2509-9
|View full text |Cite
|
Sign up to set email alerts
|

Can TKA design affect the clinical outcome? Comparison between two guided-motion systems

Abstract: Clinical study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 53 publications
3
35
2
Order By: Relevance
“…This in contrast to stiffness rates with the original BCS I design of 22.6% [7], 2.7% [6], and 2.2% [4] reported in the literature. It remains unclear whether the absence of stiffness in our series was supported by the kinematic rotational alignment obtained using an extension-first surgical technique.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…This in contrast to stiffness rates with the original BCS I design of 22.6% [7], 2.7% [6], and 2.2% [4] reported in the literature. It remains unclear whether the absence of stiffness in our series was supported by the kinematic rotational alignment obtained using an extension-first surgical technique.…”
Section: Discussioncontrasting
confidence: 59%
“…Recent data from a retrospective analysis indicated superior results with this device when compared with another guided-motion implant, the Scorpio Non-Restrictive Geometry posterior-stabilized knee system (Stryker Orthopedics, Mahwah, NJ) [6]. Patients undergoing TKA with the Journey BCS experienced statistically significantly better outcomes in the Knee Injury and Osteoarthritis Outcome Score (KOOS) subcategories of pain and quality of life, as well as in postoperative range of motion [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research presented here represents the continuation of a previously reported study [15]. All patients gave informed consent prior to being included in this retrospective study performed in accordance with the Ethical Standards of the 1964 Declaration of Helsinki as revised in 2000.…”
Section: Patientsmentioning
confidence: 99%
“…Despite the current success of total knee arthroplasty (TKA) , patellofemoral complications are a common postoperative problem and one of the causes of revision surgery [1]. The bearing geometry and kinematic pattern of different guided-motion prosthetic designs can in uence the clinical and functional outcomes and complications of TKA [2,3]. The prosthetic trochlear groove design is considered the main determinant [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%